Analisis Fiqh Siyasah Dusturiyah dalam Pembentukan Peraturan Tentang Trading in Influence dalam Hukum Positif di Indonesia - Rinaldo, M. Edwar; Pradikta, Hervin Yoki (Universitas Islam Negeri Raden Intan Lampung, 2021)
The mode of corruption and crime from time to time has undergone a significant change. This can be seen from the various corruption cases managed by law enforcers, both by the Corruption Eradication Commission, the Police and the Attorney General's Office. Influence trading in reality in the United Nation Convention Against Corruption (UNCAC) has been categorized as a form of corruption. This is regulated in article 18 of the convention. As a country that has ratified the UNCAC, Indonesia still has not regulated this trade of influence. However, if we examine a number of cases handled by law enforcers such as the KPK (Anti-Corruption Comission), it clearly has this dimension of influence. Such as the chairman of a political party and the family of a public official who takes advantage of their position and closeness to public officials. From this influence there is an undue advantage (undue advantage). In the view of Islam, this is one of the deviant behaviors that will result in a poor work ethic because it tends to give an affair or case that is not the expert. The authorship uses the method of research in a normative juridical manner, where the author uses laws, journal articles, books and documents that support in analyzing the interpretation of fiqh siyasah dusturiyah in the formation of regulations on Trading in Influence (trading influence) in positive law, its formation or by updating existing laws by accommodating the delik trading in influence contained in the UNCAC into Law No.31 of 1999 jo Law No.20 of 2001 on Corruption Crimes , with Ijtihad (ra'yu) from the role of Ahlu al halliwal Aqdhi he has the right to form and revise the rule of law in force, Consequently ratified united nation convention against corruption (UNCAC) by Indonesia through Law No. 7 of 2006 on Ratification of UNCAC is a necessity to adopt norms that are considered important into positive law in Indonesia.